Matrizes e sistemas lineares nas questões de Matemática do ENEM: análises de competências e habilidades - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
This research aims to subsidize mathematics educators towards matrices and linear systems, given the competences and abilities established by the Reference Matrix of The National Exam of High School (ENEM). For those purposes, bibliographical studies and documentary analyzes were carried out with the goal of characterizing the study of matrices and linear systems within the school environment attending to compentences and abilities. Next, some questions featured in ENEM from 2009 to 2017 were selected to be resolved by one class taking the 2nd grade and one taking the 3rd year of a rural high school in the municipality of São Miguel do Iguaçu – Paraná. This process was categorized as a study of case, reaching the competence of area 5 from the ENEM’s Reference Matrix, “Modeling and solving problems that involve socioeconomic or scientific variables, using algebraic representations”. From the application of this activity analyzes were made on the different strategies to resolving the kinds of mistakes involved, seeking to offer didactic support to the work of the teacher in the sense of developing in students the skills and abilities required.
Keywords: Matrizes; Sistemas lineares; Competências; Habilidades.; Matrices; Linear systems; Competences; Abilities; CNPQ::CIENCIAS EXATAS E DA TERRA::MATEMATICA